Effect of Physalis angulata fraction on seminiferous tubules, Bax, Bcl-2, and SOD1 mRNA expression in testicular diabetic rat model - Muhamad Tolib, Rul Afiyah Syarif, Dicky Moch Rizal, Mae Sri Hartati Wahyuningsih, Nur Arfian, Ika Rahayu, Kim Danasjz Syafeti, Frida Septiani Tavia, Saddam Muhdi (Journal of Applied Pharmaceutical Science, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease that can lead to infertility due to hypogonadism and erectile dysfunction. The increase in apoptosis caused by hyperglycemia is the main driver behind testicle weight reduction and histological changes in the testicle. Previous research showed that the administration of fraction I of Physalis angulata (Pa) had the best glucose-reducing activity compared to the other fractions on myoblast cells. This study investigated the effects of fraction I of Pa on damaged testicles in DM condition. This study used Wistar rats as an animal model of DM. Animals were induced by a single dose of streptozotocin (STZ) 60 mg/kgBW. Fractions of Pa were given once a day for 2 months at a dose of 8.5 (Pa 1), 34 (Pa 2), and 136 mg/kgBW (Pa 3). Testicular histology images were viewed using histology preparations with Hematoxylin and Eosin staining, whereas Bax, Bcl- 2, and superoxide dismutase (SOD1) mRNA expression was tested using real-time polymerase chain reaction. The results showed that the fraction of Pa improved seminiferous tubule’s diameter and its epithelial thickness in DM model animals. Administration of Pa fraction in the treatment group showed an increase in seminiferous epithelial thickness, mRNA expression of Bcl-2, and SOD1 and decreased luminal diameter of the seminiferous tubules and Bax mRNA expression compared to the DM group. This study shows that the administration of a fraction of Pa at a dose of 136 mg/kgBW provides an optimal protective effect on testicular repair caused by hyperglycemia conditions compared to other doses. There is no preceding study on the effects of a fraction of Pa extract on damaged testicles in DM condition, making this study a valuable contribution to the field.
Keywords: Active fraction, apoptosis, oxidative stress, Physalis angulata